Pengenalan Budidaya Tanaman Tomat Melalui Metode Hidroponik Di Desa Parentas Kecamatan Cigalontang Kabupaten Tasikmalaya - Mubarok, Syariful; Nuraini, Anne; Sudarjat, Sudarjat; Suminar, Erni; Qonit, Muhammad Abdilah Hasan (Jurnal ABDINUS : Jurnal Pengabdian Nusantara, 2020)
The development of plant cultivation technology is now developing rapidly. One of the technologies being developed is the technology of cultivating landless or by using a hydroponic system. Many types of hydroponics, one of which is the method of drip irrigation with planting media in the form of husk charcoal. The purpose of this activity is to introduce renewable technology to the cultivation of tomato plants to the community, so that public knowledge will increase. This activity was carried out in Parentas Village, Cigalontang District, Tasikmalaya District, with a survey method and socialization of the introduction of tomato cultivation technology through the Hydroponic system to the public. This program succeeded in informing the villagers about the cultivation techniques of tomato plants using Hydroponic technology with satisfactory results. The response of the extension participants who were enthusiastic and felt interested in the technology encouraged the participants to be willing to cultivate tomato plants with Hydroponic technology and work together to be able to produce tomato products with the technology in a sustainable manner.